Bibliometrics unleashed: navigating the landscape of classroom assessment - Wan Mat, Wan Fazwani; Lian, Lim Hooi (Journal of Education and Learning (EduLearn), 2025)
This bibliometric article examines the current state of publication in the field of classroom assessment, exploring the productivity and influence of countries, institutions, and authors. A search query of on the Scopus database using the term “classroom assessment” or “classroom-based assessment” or “assessment for learning” was performed retrieving 824 scholarly articles from 1985 to 2023. VOSviewer software was used to create maps based on network data of scientific publications displaying relationships among researchers, countries, and scientific journals. By analyzing citation patterns and keywords, it identifies popular themes among scholars and highlights areas requiring further research under keywords such as "assessment for learning", "feedback", and "validity". The study provides valuable insights into the evolving landscape of classroom assessment research, offering a comprehensive overview of the key contributors and trends shaping the field. Author keywords were used to explore the co-occurrence of different terms connected to classroom assessment. This study's findings provide a comprehensive comprehension of the current state of classroom assessment research, making a substantial contribution to the education and assessment literature and paving the way for future research directions.